2012
DOI: 10.2741/s298
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic effects of RNase-L dysregulation in immunity and proliferative control

Abstract: The endoribonuclease RNase-L is the terminal component of an RNA cleavage pathway that mediates antiviral, antiproliferative and immunomodulatory activities. Inactivation or dysregulation of RNase-L is associated with a compromised immune response and increased risk of cancer, accordingly its activity is tightly controlled and requires an allosteric activator, 2',5'-linked oligoadenylates, for enzymatic activity. The biological activities of RNase-L are a result of direct and indirect effects of RNA cleavage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 155 publications
(200 reference statements)
0
5
0
Order By: Relevance
“…Several studies have reported the antitumor effects of RNase L through several mechanisms, including the dependence on enzyme activity and regulations to specific signaling 3,14,37,38 . However, these studies mainly investigated the expression feature of RNase L and subsequent alteration of oncogenes that participated in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the antitumor effects of RNase L through several mechanisms, including the dependence on enzyme activity and regulations to specific signaling 3,14,37,38 . However, these studies mainly investigated the expression feature of RNase L and subsequent alteration of oncogenes that participated in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, by comparing lung cancer cells and normal pulmonary epithelial cells, we investigated the difference and altered phenotype that related to the function of RNase L between two kinds of cells and proposed the mechanism of how cancer cells impaired the function of RNase L. Another highlight of the present study is the function of RNase L in the nucleus. Previous studies focused on the function of RNase L in the cytoplasm that regulates signaling or molecules involved in cancer progression 3,14,38 . In our research, we found that RNase L was also located at the nucleus with high expression level both in lung epithelial cells and cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…(6567) RNASEL variants have been associated with elevated inflammatory biomarkers(68) and the enzyme encoded by the RNASEL gene has proinflammatory functions. (69)…”
Section: Discussionmentioning
confidence: 99%
“…RNASEL plays a significant role in viral clearance and it has been suggested that variation in RNASEL may alter risk of viral-associated cancers, such as head and neck squamous cell carcinoma and cervical cancer, as well as non-viral cancers such as breast cancer [45], [46]. Discrepancies between large studies of hereditary prostate cancer suggest that environmental factors, such as viral infection, may modulate the impact of RNASEL variation on carcinogenesis [18].…”
Section: Discussionmentioning
confidence: 99%